Analysis of Water Loss Management Performance of Water Utilities and Development of Basic Performance Indicator Analysis Tool - Mahmut Fırat; Cansu Orhan; Salih Yılmaz; Özgür Özdemir (Doğal Afetler ve Çevre Dergisi)
In water loss management, monitoring system behavior and analyzing system performance according to appropriate indicators is very important for improving operating conditions. However, appropriate calculation tools should be used to make these analyzes accurately, regularly, systematically and precisely. Therefore, in this study, the most appropriate indicators were determined based on the indicators proposed IWA and other organizations in literature in order to analyze and monitor the process performance in water loss management. A web-based "GGS basic performance analysis calculation tool" has been developed to systematically calculate these indicators and monitor performance. This tool basically includes volumetric and percentage indicators, service connection and per line length indicators, administrative and physical loss, economic and cost, failure and network rehabilitation indicators. The details of this tool were detailed, its advantages were discussed by analyzing of sample data set. It is believed that this analysis tool developed in this study will provide significant contributions to the analysis and monitoring of the performance of the Utilities in terms of water loss management and its components, and to evaluate the process performance for active leakage control activities